2006
DOI: 10.1001/archotol.132.11.1196
|View full text |Cite
|
Sign up to set email alerts
|

Up-regulation of Peroxisome Proliferator-Activated Receptor γ in Perennial Allergic Rhinitis

Abstract: To investigate the expression of peroxisome proliferator-activated receptor ␥ (PPAR-␥) messenger RNA and protein and to localize the PPAR-␥ protein in the nasal mucosa of patients with allergic rhinitis and control subjects.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
7
0

Year Published

2009
2009
2020
2020

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 9 publications
(7 citation statements)
references
References 16 publications
0
7
0
Order By: Relevance
“…2 In addition, PPAR-γ is expressed in human nasal mucosa and upregulated in patients with perennial allergic rhinitis (AR). 3 In a murine model of experimental AR, PPAR-γ activation effectively inhibited allergic symptoms, nasal mucosa inflammation, the production of antigen-specific immunoglobulin E (IgE) and Th2-type cytokines, and suppressed the overexpression of galectin-3 induced by ovalbumin (OVA). 4,5 AR is one of the most common chronic diseases in the industrialized world.…”
mentioning
confidence: 99%
“…2 In addition, PPAR-γ is expressed in human nasal mucosa and upregulated in patients with perennial allergic rhinitis (AR). 3 In a murine model of experimental AR, PPAR-γ activation effectively inhibited allergic symptoms, nasal mucosa inflammation, the production of antigen-specific immunoglobulin E (IgE) and Th2-type cytokines, and suppressed the overexpression of galectin-3 induced by ovalbumin (OVA). 4,5 AR is one of the most common chronic diseases in the industrialized world.…”
mentioning
confidence: 99%
“…Other groups have reported that PPARγ is expressed in epithelium, smooth muscles, mucous glands, and infiltrating inflammatory cells in nasal polyps or nasal mucosa [23,24]. Further studies will be needed to clarify the expression of PPARγ in epithelium and mucous glands in nasal tissues.…”
Section: Discussionmentioning
confidence: 97%
“…Recently, PPARγ expression has been found in eosinophils and mast cells, which are types of immune cells [4,25]. Additionally, Kang et al reported that the expression of PPARγ mRNA and protein in the nasal mucosa increased in patients with perennial allergic rhinitis [26]. Thus, it is suggested that the activation of PPARγ negatively controls the activation of mast cells.…”
Section: Discussionmentioning
confidence: 99%